RELEVANSI PERUBAHAN KURIKULUM 2013 TERHADAP KURIKULUM MERDEKA BELAJAR DI ERA DIGITAL - Muhammad Nasrul Waton (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
The curriculum is a very important part of the educational process, because the curriculum is the main substance in the material being taught. The Minister of Education and Culture of the Republic of Indonesia emphasized the need for changes and developments in the 2013 curriculum Besides that, the 2013 curriculum also develops information and communication technology literacy, as well as strengthening character education in character building and spiritual values. All education standards in Indonesia are formulated into the Indonesian Partnership for 21st Century Skill Standards. The author takes a study where the curriculum was made when the times were so fast with the use of technology, namely the 2013 curriculum or better known as K13 with the independent learning curriculum. The rapid changes in the Indonesian education curriculum where the 2013 curriculum has begun to be seen and can be felt has born a new system, a new curriculum that is echoed as the Independent Curriculum which has started in the 2022/2023 school year. This research uses a systematic review approach because the writing of this article is based on several references in the form of books and articles as well as scientific publications online. The 2013 curriculum is a competency and character-based curriculum that aims to increase educational attainment and is expected to produce productive, creative, innovative and effective young people. independent learning focuses on the freedom to learn independently and creatively. It is very appropriate that now a different curriculum is needed from the previous curriculum in dealing with the digital era.